(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
This article presents a comparative study of the pragmatic features of numbers in English and Uzbek languages. We explore how speakers of these languages use numbers in different contexts to convey meaning beyond their literal value. The study focuses on three main areas: (1) the use of numbers in counting and measuring, (2) the use of numbers in expressing time and dates, and (3) the use of numbers in expressing quantities and statistics. Through a detailed analysis of examples from both languages, we demonstrate how pragmatic factors such as context, speaker intention, and cultural norms play a crucial role in shaping the meaning of numbers. The article concludes by highlighting the importance of understanding these pragmatic features for effective communication across different languages and cultures. Overall, this study provides valuable insights into the role of pragmatics in shaping language use and meaning.